2022
DOI: 10.1007/s00432-022-03944-z
|View full text |Cite
|
Sign up to set email alerts
|

Response prediction in patients with gastric and esophagogastric adenocarcinoma under neoadjuvant chemotherapy using targeted gene expression analysis and next-generation sequencing in pre-therapeutic biopsies

Abstract: Objectives Perioperative chemo-(radio-) therapy is the accepted standard in European patients with locally advanced adenocarcinoma of the esophagogastric junction or stomach (AEG/AS). However, 30–85% of patients do not respond to this treatment. The aim of our study was the identification of predictive biomarkers in pre-therapeutic endoscopic tumor biopsies from patients with histopathologic response (Becker-1) versus non-response (Becker-2/3) to preoperative chemotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Other somatic variations, such as C10orf71 mutation and MDM2 amplification, also correlated closely with gastric cancer NAC outcomes [ 57 ]. Correspondingly, another translational study confirmed high single-nucleotide variant (SNV) in Becker-3 gastric cancer patients; however, DNA cluster alteration was not detected based on the TRG after NAC [ 58 ]. In addition to genomic changes in primary tumors, other factors related to the tumor immune microenvironment also contribute to the response to NAC, and are correlated with long-term survival.…”
Section: Predictors Of Nac Outcomes In Gastric Cancermentioning
confidence: 99%
“…Other somatic variations, such as C10orf71 mutation and MDM2 amplification, also correlated closely with gastric cancer NAC outcomes [ 57 ]. Correspondingly, another translational study confirmed high single-nucleotide variant (SNV) in Becker-3 gastric cancer patients; however, DNA cluster alteration was not detected based on the TRG after NAC [ 58 ]. In addition to genomic changes in primary tumors, other factors related to the tumor immune microenvironment also contribute to the response to NAC, and are correlated with long-term survival.…”
Section: Predictors Of Nac Outcomes In Gastric Cancermentioning
confidence: 99%